First Finding of the Emerging Pathogen Escherichia marmotae in the Arctic - B. I. Aslanov; A. E. Goncharov; V. V. Kolodzhieva; D. V. Azarov (Эпидемиология и вакцинопрофилактика, 2024)
Relevance. Escherichia marmotae is a recently described species of Escherichia that is considered a potential new zoonotic pathogen. The geographical distribution of this microorganism in wild animals and its genomic diversity are currently insufficiently studied. Aims. The purpose of the study was to determine the pathogenic potential of the Escherichia marmotae 16guk strain isolated from zoogenic material on Hooker Island (Arkhangelsk Region, Franz Josef Land Archipelago) and its phylogenetic relationships with previously described strains of different origin. Materials and methods. The Escherichia marmotae 16guk strain was isolated from the faeces of an arctic fox (Vulpes lagopus) near a breeding ground. The pathogenic potential of the strain was assessed on the basis of genomic sequencing data using Illumina technology, an estimate of the mean lethal dose when administered intraperitoneally to mice, and an assessment of the antibiotic resistance phenotype using the disc diffusion method. To determine the phylogenetic position of the described strain within the overall structure of the microbial population, genome-wide sequencing data deposited in NCBI GeneBank were used. The phylogenomic analysis was performed based on the distance matrix of single nucleotide polymorphisms in the core genome due Parsnp. Results. The strain is characterized by low virulence when tested on mice (LD50 was 1.3*109 K.O.E.), has resistance to ampicillin and gentamicin. A number of pathogenicity factors have been identified in the genome structure, which includes siderophores of enterobactin and aerobactin operons, fimbria type I genes characteristic of extraintestinal Escherichia strains, amyloid-like protein villi (curli) and capsular genes, as well as the ibeABC invasion factor operon. The resistome is represented by blaEC15 beta-lactamase genes and acrAD-TolC efflux pump genes. According to the results of phylogenomic analysis, the strain under study shows the greatest similarity with the genome sequences of strains circulating in New Zealand and Germany among wild animals (wild boars) and birds. The similarity of the genomes of strains distributed in distant geographical regions and the isolation of the 16guk strain within an ornithogenic ecosystem can be interpreted as a result of the spread of E. marmotae with migratory birds. Conclusions. The discovery of the Escherichia marmotae 16guk strain in one of the most remote Arctic territories demonstrates the possibility of the emergence and circulation of enterobacteria strains with significant pathogenic potential in the island territories of the high-latitude Arctic, which actualizes the need for systematic monitoring studies in this region.